2021
DOI: 10.1055/a-1499-7829
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cocoa Bean Shell Antimicrobial Activity: A Tentative Assay Using a Metabolomic Approach for Active Compound Identification

Abstract: Cocoa bean shell is one of the main by-products of chocolate manufacturing and possesses several compounds with biofunctionalities. It can function as an antibacterial agent, and its action is mostly reported against Streptococcus mutans. However, only a few studies have investigated the cocoa bean shell compounds responsible for this activity. This study aimed to evaluate several extracts of cocoa bean shells from different geographical origins and cocoa varieties and estimate their antimicrobial properties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These compounds present in cocoa by-products have shown various biological effects 2 . Among the bio-functionalities of the cocoa shell, it is postulated as an antibacterial agent, inhibiting the activity against Streptococcus mutans 11 . Rossin et al 12 have reported a preventive effect against damage associated with intestinal integrity from oxidative/inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds present in cocoa by-products have shown various biological effects 2 . Among the bio-functionalities of the cocoa shell, it is postulated as an antibacterial agent, inhibiting the activity against Streptococcus mutans 11 . Rossin et al 12 have reported a preventive effect against damage associated with intestinal integrity from oxidative/inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Tamrin et al, 2020 [89] reported similar antibacterial activities related to CBS extracts (aqueous, ethanolic, methanolic and acetone) against E. coli, B. cereus and S. aureus (approximately 7 mm inhibition zone). Moreover, Rojo-Poveda et al, 2021 [90] tested the antimicrobial capacity of CBS extracts at different concentrations (0.004 to 0.5 mg of dry extract per ml) in eight bacterial and fungal strains. These authors found that inhibition was only detected at the maximum concentration (0.5 mg/mL) against E. coli, Pseudomonas aeruginosa, Saccharomyces cerevisiae, Candida albicans, methicillin-resistant S. aureus (MRSA) and methicillin-sensitive S. aureus (MSSA).…”
Section: Antimicrobial Compoundsmentioning
confidence: 99%
“…In both experiments, reductions in plaque index and caries scores were obtained by using cocoa bean husk extract at concentrations higher than 0.5 mg/mL and 1.0 mg/mL, respectively [ 44 ]. In addition, a recent study that investigated the antimicrobial effect of several extracts obtained from a variety of cocoa beans from different origins reported that almost all of the tested extracts showed activity against S. mutans [ 50 ].…”
Section: Biological Properties Of Cocoa and Oral Healthmentioning
confidence: 99%